Utilization of cull chicken (Gallus gallus domesticus, Linn.) in the production of corned chicken - Mercado, Concepcion Raquel L.
This study aims to determine whether cull chicken meat can be utilized as a primary raw material in the production of corned chicken. But to date, nothing has yet been written about the quality characteristics of corned chicken. For this reason, the first phase of this study was devoted to the assessment of the existing brand of corned chicken product in the market. Although there was no formulation and process available for corned chicken. Grammix had one for corned beef. This was therefore, used as a basis for the development of the formulation and process for corned chicken in Phase II. Three different corned chicken formulations were prepared using: (1) 60% cull chicken meat (CCN) and 40% beef; (2) 70% CCM and 30% beef and (3) 100% CCM. This was done to determine the best corned chicken product. results indicated that the best meat combination was 70% CCM and 30% beef. Relative to flavor, it was observed that the amount of salt in the Grammix formulation needed to be reduced by one-half (1/2). To further improve flavor and texture, various levels of beef tallow was substituted for corresponding amounts of cull chicken meat in the formulation. Two samples of corned chicken were prepared: one using a 10% beef tallow substituted for cull chicken meat and beef and another with 15% beef tallow. Results indicated that the product is greatly improved by using the 10% beef tallow substitution for cull chicken meat in the corned chicken formulation. Three trials of bench scale production was done using the formulation developed in Phase II. The products of the bench scale production were presented for consumer acceptability tests. Results indicated moderate acceptability for the corned chicken. Production cost estimates showed that the product can compete with corned chicken products existing in the market.